Stable Arterial Perforators Mapping in Lower Leg Using Color-Coded Doppler Sonography, Acoustic Doppler, and Thermal Imaging Camera in Patients Undergoing Digital Subtraction Angiography - Lovětínská, Vanesa; Sukop, Andrej; Sulženko, Jakub; Hora, Adam; Patzelt, Matěj; Kožnar, Boris; Kovačič, Karol; Kamenistý, Michal; Kučerák, Jozef (Journal of Reconstructive Microsurgery Open, 2024)
Background Chronic defects in the lower leg present significant challenges in plastic surgery due to their diverse etiologies and association with impaired peripheral circulation. This study describes the localization of stable perforators and assesses their changing velocities after digital subtraction angiography (DSA) and alterations of flow characteristics.Methods Ten patients with lower extremity defects requiring DSA had undergone examinations by using standard methods. The localization of 40 stable perforators originating from the anterior tibial artery, posterior tibial artery, fibular artery, and medial sural artery was performed before and after angiography. Where stenoses or occlusions were observed, percutaneous transluminal angioplasty (PTA) was conducted, and velocity changes following reperfusion were measured.Results Angiographic abnormalities were observed in all of patients, thus necessitating PTA interventions. Prior to PTA, handheld acoustic Dopplers detected 37 out of 40 perforators (90%), whereas color-coded sonography detected 35 out of 40 perforators (87.5%). After PTA, these numbers increased to 38 out of 40 (95%) and 37 out of 40 (92.5%), respectively. The diameter of the perforators ranged between 1.14 and 1.16 mm. The mean flow characteristics included the peak systolic velocities (PSV) of 21.9 and 27.2, end-diastolic velocities (EDV) of 9.4 and 11.4, and resistance indexes (RI) of 0.63 and 0.71, respectively. In the postintervention period, 16 microvessels exhibited enlarged lumen diameters ranging from 1 to 3 mm, resulting in increased perfusion values for PSV in 85.2% (21.9/27.2) and EDV in 88.2% (9.4/11.4) of the patients. The RI increased from 0.63 to 0.71. However, two perforators showed decreases in flow velocity after PTA.Conclusion In most patients with chronic lower leg wounds and other comorbidities, adequate perforators for reconstruction can be identified by using conventional methods. PTA interventions positively impact blood flow in perforators, although they are not necessarily required prior to reconstruction.
Keywords: acoustic doppler; color-coded duplex; DSA; perforator; PTA; thermal imaging camera